Efektifitas Terapi Slow Stroke Back Massage Terhadap Nyeri Kepala Pasien Hipertensi - Defrima Oka Surya; Viki Yusri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: In patients with hypertension, headaches will usually appear which are felt by more than 50% of hypertensive patients. Headaches if left untreated can cause sleep disturbances, disturbances in daily activities, emotional disturbances and can even reduce the quality of life of hypertensive patients. Complementary therapy can be one of the nursing interventions for the management of hypertension. One of the complementary therapies that can be used is slow stroke back massage (SSBM). SSBM therapy is carried out by massaging the back area which provides cutaneous stimulation so that it has a relaxing effect.Objective: To determine the effectiveness of slow stroke back massage (SSBM) on headache in hypertensive patientsResearch Methods: This research is a quantitative study with a quasi-experimental design approach using a one group pre and post test approach without control group design. The research was conducted in the Working Area of the Lubuk Buaya Health Center, Padang. Sampling was done by consecutive sampling technique with a sample size of 21 people. SSBM intervention was carried out for 6 days. Headache scale before and after intervention was assessed by Numeric Rating Scale (NRS)Research Results: The average headache scale before SSBM administration was 5.48 and after SSBM administration was 2.24. Based on the statistical t-dependent test, it was found that p value = 0.000 (ρ<0.05), meaning that SSBM was effective in overcoming the problem of headache in hypertensive patients in the Lubuk Buaya Padang Health Center Work Area.Conclusion: SSBM can be used for the treatment of hypertension in overcoming the problem of headache in hypertensive patients